RE-PLACEING THE CITY: DIGITAL NAVIGATION TECHNOLOGIES AND THE EXPERIENCE OF URBAN PLACE - Halegoua, Germaine (AoIR Selected Papers of Internet Research, 2015)
This paper combines media and cultural studies, science and technology studies, geography and urban studies approaches in order to investigate navigation technology users’ understandings of their own spatial relations and conditions of mobility. Through interviews and questionnaires with 132 navigation technology users, this paper identifies the ways that people actually use digital navigation technologies, why they use these technologies, how these technologies influence their physical movement, and how navigation technology users cognitively map and understand their embeddedness within urban space. In addition to interviews and surveys with members of this group, this paper also analyzes the ways in which digital spatial navigation has been constructed in popular culture, press releases, advertisements, and legal documents and how these texts contribute to users’ understandings of digital navigation technologies and placemaking. Through the intersections of marketing campaigns, popular discourse, regulation, and actual practices I investigate how the social and technological construction of place is experienced and understood through services and practices of digital navigation. Ultimately, I analyze the ways in which digital navigation technology use encourages pedestrians and motor vehicle operators to re-place the unknown, unfamiliar space of the city as a manageable, organized, bounded space and how this understanding of space allows for a deeper sense of place on the part of digital media users. Although navigation technology non-use is not directly addressed in this paper, I will present some preliminary findings regarding non-use that were gathered as part of the questionnaire process. The findings presented in this paper urge researchers to rethink what we know about the use of navigation technologies in urban space and to reconsider how these technologies help users cultivate a sense of place, rather than distract them from their surroundings.